Changes in nitrogen cycling during the past century in a northern hardwood forest - McLauchlan, Kendra K.; Craine, Joseph M.; Oswald, W. Wyatt; Leavitt, Peter R.; Likens, Gene E. (My University, 2007)
Nitrogen (N) availability, defined here as the supply of N to terrestrial plants and soil microorganisms relative to their N demands, limits the productivity of many temperate zone forests and in part determines ecosystem carbon (C) content. Despite multidecadal monitoring of N in streams, the long-term record of N availability in forests of the northeastern United States is largely unknown. Therefore, although these forests have been receiving anthropogenic N deposition for the past few decades, it is still uncertain whether terrestrial N availability has changed during this time and, subsequently, whether forest ecosystems have responded to increased N deposition. Here, we used stable N isotopes in tree rings and lake sediments to demonstrate that N availability in a northeastern forest has declined over the past 75 years, likely because of ecosystem recovery from Euro-American land use. Forest N availability has only recently returned to levels forecast from presettlement trajectories, rendering the trajectory of future forest N cycling uncertain. Our results suggest that chronic disturbances caused by humans, especially logging and agriculture, are major drivers of terrestrial N cycling in forest ecosystems today, even a century after cessation.
Keywords: 15N; Land use history; Mirror Lake; Nitrogen availability; Paleoecology